Pengaruh Metode Edutainment terhadap Keterampilan Bahasa Arab Kelas V di Sekolah Dasar - Azahra, Tiara Mudi; Rahman, Alvin Yanuar; Ramadhan, Dadan Fitria (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research describes the influence of the editing method on Arabic speaking skills in fifth grade elementary school. Low speaking skills are caused by several factors, one of which is the application of less effective learning methods. Students' speaking skills can be improved by improving learning methods. There are many interactive learning methods that can be applied, researchers apply the edutainment method as a form of treatment in the experimental class and the jigsaw method as a comparison method in the control class. The type of research used is quasi-experimental with a quantitative approach. The data collection techniques used were tests and documentation. This research was carried out over four meetings. The population in this study were all students at SD IT Bina Insan Qur'ani. The sample in this study was class V-A with a total of 23 students, and class V-B with a total of 22 students. The results of the research show that there is a difference in the average value of improvement in Arabic speaking skills for students who use the edutainment method and students who use the jigsaw method.